Enhancing dna immunization by targeting asfv antigens to sla-ii bearing cells - Argilaguet, J. M. (2011)
One of the main criticisms to DNA vaccines is the poor immunogenicity that they confer on occasions, at least in large animals. Confirming this theory, immunization with plasmid DNA encoding two African swine fever virus genes in frame (pCMV-PQ), failed in inducing detectable immune responses in pigs, while it was successful in mice. Aiming to improve the immune responses induced in swine, a new plasmid was constructed, encoding the viral genes fused in frame with a single chain variable fragment of an antibody specific for a swine leukocyte antigen II (pCMV-APCH1PQ). Our results clearly demonstrate that targeting antigens to antigen professional cells exponentially enhanced the immune response induced in pigs, albeit that the DNA vaccine was not able to confer protection against lethal viral challenge. Indeed, a viremia exacerbation was observed in each of the pigs that received the pCMV-APCH1PQ plasmid, this correlating with the presence of non-neutralizing antibodies and antigen-specific SLA II-restricted T-cells. The implications of our discoveries for the development of future vaccines against African swine fever virus and other swine pathogens are discussed.